Combination hyperbaric oxygen and temozolomide therapy in c6 rat glioma model - Dagıstan,Yaşar (2012)
PURPOSE: Temozolomide (TMZ) has anti-tumor activity in patients with malignant glioma. Hyperbaric oxygen (HBO) may enhance the efficacy of certain therapies that are limited because of the hypoxic tumor microenvironment. We examined the combined effects of TMZ-HBO in a rat glioma model. METHODS: After stereotactic injection of C6/LacZ rat glioma cells into the Wistar rats brain, the rats were randomly assigned to three treatment groups [group 1, control treatment; group 2, TMZ alone; group 3, a combination of TMZ and HBO]. Rats were sacrificed 18 days after treatment, and number of intra-/peri-tumoral vessels, microendothelial proliferations, immunohistochemistry and necrotic area were evaluated. RESULTS: Tumoral tissue was stained only sparsely with GFAP. Temozolomide treatment was significantly decreased in tumor tissue intratumoral vessel number / total tumor area level. The level of Ki67 was significantly decreased in the tumor tissue of the group 3. Additionally, the total necrotic area / total tumor volume (%) was decreased significantly in tumor tissue of the group 3 rats compared to group1 and 2. CONCLUSION: The combination of hyperbaric oxygen with temozolomide produced an important reduction in glioma growth and effective approach to the treatment of glioblastoma.